Low-temperature enhances production of severe fever with thrombocytopenia syndrome virus virus-like particles - Loop, Isabelle; Ke, Yuan-Dun; Chen, Wei-June; Tsai, Kun-Hsien; Hsu, Wei-Li; Fan, Yi-Chin (Applied microbiology and biotechnology, 2025)
Tick-borne severe fever with thrombocytopenia syndrome (SFTS) is an emerging zoonotic disease caused by the SFTS virus (SFTSV). Serological assays based on the nucleocapsid protein and partial glycoprotein of this virus have been used for detecting SFTSV infections in humans and animals. However, whether the complete SFTSV glycoprotein (Gn/Gc) can induce the assembly of virus-like particles (VLPs) which can be used for serological surveillance and vaccine production remains unclear. In this study, we successfully expressed and secreted SFTSV Gn/Gc antigens by using a single plasmid encoding the complete glycoprotein sequence of the dominant genotype B virus. HEK293T and COS-1 cells were transfected with the aforementioned plasmid; cultivating these cells at 32 °C, instead of 37 °C, led to 4.0- and 3.3-fold higher antigen recovery, respectively. The secreted Gn/Gc antigens at 32 °C retained epitopes resembling those of the virion; these epitopes were recognized by a SFTS human–derived monoclonal antibody. Sucrose density gradient centrifugation, followed by transmission electron microscopy, confirmed the formation of VLPs with a diameter of approximately 100 nm. Overall, our findings highlight the potential of SFTSV VLPs for serological surveillance and vaccine development. Key points • Cultivating transfected cells at 32 °C boosts SFTSV glycoprotein production. • Complete SFTSV glycoprotein expression facilitates virus-like particle assembly. • The assembly does not require any other viral proteins or RNA.